Desenvolvimento de campanhas educacionais em prol do uso racional da água em instituições de ensino superior - Alves, Davi Wesley Moreira (Universidade Federal Rural do Semi-Árido, 2021)
Recognizing the importance of rational use of water, in line with the Sustainable Development Goals (SDGs) of the UN Agenda 2030, more specifically with SDG 6 (clean water and sanitation), the need for the commitment of Higher Education Institutions is highlighted ( IES) with this theme. In this sense, this work aimed to develop educational campaigns in favor of the rational use of water at the Federal Rural University of the Semi-Árido (UFERSA), campus Mossoró, under the project “Guidelines for the Elaboration of a Rational Use Plan for the Water at UFERSA (DEPURA)”. The information base for the proposals was based on the DEPURA project database, relevant to the typology, consumption and waste of water in sanitary appliances and laboratory equipment with high water consumption, measured in university buildings. For that, a content curatorship was carried out to subsidize the production of educational graphic materials. For this construction, a method for the development of a design project was applied. These materials were submitted to consultation with the Ufersian community, through questionnaires and, later, improved. As a result, 16 portfolios were produced, based on content curation, aimed at different target audiences (general public, teachers and students, technicians and management). In terms of training and mobilization of the campaigns, the International Workshop on the Rational Use of Water (WIURA) was held, promoted by the research group System for Management and Effectiveness of Water Conservation (SIGECA), from which the DEPURA project is derived, to promote discussions on the thematic rational use of water with international and national educational and research institutions. In this perspective, an evaluation of the first edition of the WUIRA was carried out to propose alternatives for future events, in addition to the development of a new wireframe for the DEPURA project website, by applying the concepts of user experience (UX) and user design interface (UI). The results obtained can be used as strategies in the promotion of environmental education, training and mobilization actions both in the scope of the DEPURA project and in the sphere of UFERSA's Sustainable Logistics Management Plan
Keywords: Desenvolvimento sustentável; Água limpa; Universidade; Sustainable Development; Clean water and sanitation; University; ENGENHARIAS::ENGENHARIA CIVIL; Esgotamento sanitário